Nieważność miejscowego planu zagospodarowania przestrzennego - Zwolak, Sławomir (Studia Prawa Publicznego, 2025)
The article is devoted to the issue of the grounds for challenging a local spatial development plan. The case law of administrative courts indicates that there may be many of these grounds, but the most important are a violation of the planning procedure, placing the complainant in a worse position than the owners of other properties covered by the plan, limiting rights to land contrary to the principle of proportionality, or inconsistency of the provisions of the local plan with the provisions of the general plan. However, a common feature of all the grounds is a conﬂict with the law, i.e. the local plan’s non-compliance with the law. This means that this conﬂict must be clear in its content, and directly contravene the provision of law. A contradiction of the resolution on the adoption of the local plan due to a violation of generally applicable legal acts constitutes a basis for declaring the local plan invalid. However, the Spatial Planning and Development Act does not specify what violations should be considered signiﬁcant, therefore the assessment of the gravity of the violation is left to the practice and experience of supervisory authorities and administrative courts. In particular, signiﬁcant violations include not only exceeding the principles of drawing up a local plan but also exceeding the planning authority of the commune. The latter occurs when the plan introduces property restrictions that are inconsistent with the constitutional principle of equality or the principle of proportionality, and which differentiate the legal position of their owners in relation to neighbouring lands covered by the local plan. The occurrence of at least one of the premises causing a violation of the requirements for the adoption of a local plan will result in its invalidity.